Proliferative potential and phenotypic analysis of long-term cultivated human granulosa cells initiated by addition of follicular fluid - Bruckova, Lenka; Soukup, Tomas; Visek, Benjamin; Moos, Jiri; Moosova, Martina; Pavelkova, Jana; Rezabek, Karel; Kucerova, Lenka; Micuda, Stanislav; Brcakova, Eva; Mokry, Jaroslav (Journal of assisted reproduction and genetics, 2011)
PURPOSE: The aim of this study was to develop and optimize a strategy for long-term cultivation of luteinizing human granulosa cells (GCs). METHODS: GCs were cultivated in DMEM/F12 medium supplemented with 2% fetal calf serum. In vitro proliferation of GCs was supported by follicular fluid as well as FSH and growth factors. RESULTS: The cultured GCs were maintained for 45 days with a doubling time of 159 ± 24 h. GCs initiated by the addition of follicular fluid and cultivated under low serum conditions reached 10 ± 0.7 population doublings. GCs maintain the typical phenotypic expression and the telomere length according to specific culture conditions. CONCLUSION: Our present study has demonstrated that GCs can be maintained in vitro for at least 45 days and this cell model can be beneficial when studying hormonal regulation associated with follicular maturation and preparation of oocytes for fertilization.
Keywords: Granulosa Cells; folikulární tekutina; Humans; telomery; Follicular Fluid; Female; Phenotype; lidé; proliferace buněk; Cells, Cultured; časové faktory; Telomere; folikulární buňky; ženské pohlaví; Flow Cytometry; fenotyp; Cell Proliferation; kultivované buňky; karyotypizace; průtoková cytometrie; Cell Culture Techniques; Time Factors; Karyotyping; buněčné kultury